Fibrin glue-induced eosinophilic pleural effusion after pulmonary resection: A case report. (August 2021) - Kawamoto, Nobutaka; Okita, Riki; Okada, Masanori; Ito, Kosuke; Hirazawa, Katsutoshi; Inokawa, Hidetoshi
Abstract: Introduction and importance: Prolonged air leakage after pulmonary resection is a common complication, and fibrin glue is used as a sealant to reduce this. Fibrin glue-induced adverse events are generally rare. Herein, we describe a rare case of fibrin glue-induced eosinophilic pleural effusion (EPE). Case presentation: A 77-year-old man underwent partial pulmonary resection for right lower lobe lung cancer, and the pulmonary staple stump was subsequently covered with fibrin glue. Antibacterial drugs were administered for the treatment of postoperative pneumonia. However, re-elevation of the inflammatory cell number was observed, and computed tomography revealed an increase in right pleural effusion. Although thoracoscopy was performed based on a possibility of empyema, no empyema was observed. The eosinophil count in the pleural effusion was 11%; thus, the patient was diagnosed with EPE, which was resolved after thoracic drainage, without corticosteroid administration. Fibrin glue was identified as the causative agent, using a drug-induced lymphocyte stimulation test. Clinical discussion: EPE is defined as an eosinophil count of ≥10% in the pleural effusion. If pleural effusion on the surgical side, with fever or an elevated inflammatory cell number, is observed in the early postoperative period after pulmonary resection, empyema should be considered foremost. In this case, the administration of antibacterial drugs was ineffective, and the patient was eventually diagnosed with EPE. Conclusion: EPE should be considered as a rare fibrin glue-induced adverse event after pulmonary resection. It is recommended that the leukocyte fraction be examined, if pleural effusion is collected for postoperative pleural effusion. Highlights: Fibrin glue is used as a sealant to reduce air leakage after pulmonary resection. A rare case report of fibrin glue-induced eosinophilic pleural effusion (EPE). After pulmonary resection, clinical course of EPE is similar to that of empyema. Examination of leukocyte fraction in pleural effusion is useful for EPE diagnosis. Thoracic drainage is a useful treatment option for fibrin glue-induced EPE.